Effect of void fraction models on the two-phase friction factor of R134a during condensation in vertical downward flow in a smooth tube - Dalkilic, A. S.; Laohalertdecha, S.; Wongwises, S. (PERGAMON-ELSEVIER SCIENCE LTD, 2008)
The void fraction of R134a condensing inside a vertical smooth tube is experimentally investigated in this study. The vertical test section is a 0.5 m long countercurrent flow double tube heat exchanger with refrigerant flowing down the inner tube and cooling water flowing upward in the annulus. The inner tube is made from smooth copper tubing and has an 8.1 mm inner diameter. The test runs are done at an average saturated condensing temperature of 40 degrees C. The average qualities are between 0.8 and 0.99 while the mass fluxes are 300 kg m(-2) s(-1) and the heat fluxes are between 22 and 39.8 kW m(-2). The void fractions are indirectly determined using relevant measured data together with various void fraction models and correlations reported in the open literature. The friction factors obtained from various void fraction models and correlations are compared with each other and also with those determined from graphical information provided by Bergelin et al. The effect of void fraction alteration on the momentum pressure drop is also presented. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: heat transfer; void fraction; friction factor; condensation; downward flow; R134a; PRESSURE-DROP; PREDICTION; GAS; Thermodynamics; Mechanics